2019
DOI: 10.1002/ejp.1489
|View full text |Cite
|
Sign up to set email alerts
|

Combined pulsed and thermal radiofrequency versus thermal radiofrequency alone in the treatment of recurrent trigeminal neuralgia after microvascular decompression: A double blinded comparative study

Abstract: Background: Recurrent trigeminal neuralgia (RTN) is a common clinical problem and pain recurs in many patients after microvascular decompression (MVD). We evaluated the effect of adding pulsed radiofrequency to radiofrequency thermocoagulation at 60°C compared to radiofrequency thermocoagulation at 70°C alone in the treatment of recurrent trigeminal neuralgia after microvascular decompression. Methods: 40 patients with recurrent trigeminal neuralgia after microvascular decompression were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…17 Compared with percutaneous balloon compression, stereotactic radiosurgery, and radiofrequency thermocoagulation, all of which are associated with a high likelihood of recurrence and sensory deficits, redo-MVD reportedly has good outcomes in the management of recurrent TN. [18][19][20] Recurrence in 64 of 137 patients in this study was due to incomplete or absent decompression or new responsible vessels. To ensure thorough pain relief, redo-MVD should include decompression of both the trigeminal root entry zone and the peripheral nerve segments, where blood vessels can cause symptoms.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…17 Compared with percutaneous balloon compression, stereotactic radiosurgery, and radiofrequency thermocoagulation, all of which are associated with a high likelihood of recurrence and sensory deficits, redo-MVD reportedly has good outcomes in the management of recurrent TN. [18][19][20] Recurrence in 64 of 137 patients in this study was due to incomplete or absent decompression or new responsible vessels. To ensure thorough pain relief, redo-MVD should include decompression of both the trigeminal root entry zone and the peripheral nerve segments, where blood vessels can cause symptoms.…”
Section: Discussionmentioning
confidence: 69%
“… 17 Compared with percutaneous balloon compression, stereotactic radiosurgery, and radiofrequency thermocoagulation, all of which are associated with a high likelihood of recurrence and sensory deficits, redo-MVD reportedly has good outcomes in the management of recurrent TN. 18 20 …”
Section: Discussionmentioning
confidence: 99%
“…Rarely, CSF leak, carotid-cavernous fistula, meningitis, and anesthesia dolorosa/trigeminal deafferentation pain may be encountered. 120,[166][167][168][169][170][171][172][173][174][175][176][177][178][179][180]…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…The patients will be assigned to either of the following groups, determined by the envelopes opened by the study nurse. Two hertz of PRF will be administered at a voltage of 70 V, temperature of 42°C, pulse width of 20 ms, and treatment time of 600 s. (29,31) Then low-temperature CRF will be performed at 60°C, with a treatment time of 270 s (31,33).…”
Section: Trial Interventionsmentioning
confidence: 99%
“…In a retrospective study, PRF combined with CRF at 68°C was more effective than CRF alone (97.5% vs. 87.5%) after 1 year, along with fewer side effects and faster recovery times (32). The most recent randomized controlled trial found that PRF, combined with CRF at 60°C, for the treatment of recurrent trigeminal neuralgia after microvascular decompression, resulted in fewer side effects and complications with a similar effectiveness to CRF at 70°C (33). Currently, there is no consensus on the treatment parameters for PRF combined with CRF; including treatment time, temperature, and voltage.…”
mentioning
confidence: 99%